Technical Aspects in Esophageal Lengthening: An Investigation of Traction Procedures and Suturing Techniques in Swine - Oetzmann von Sochaczewski, Christina; Tagkalos, Evangelos; Lindner, Andreas; Lang, Hauke; Heimann, Axel; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2019)
Introduction Traction procedures are useful to preserve the child's own esophagus in long-gap forms of esophageal atresia. To date, it remains unclear what suture size or position of the traction sutures is optimal to account for differences in anatomy and to reduce the risk of traction sutures being torn out of the esophageal tissue.Materials and Methods Explanted porcine esophagi (from swine aged 100–120 days and weighing 100–120 kg) were divided at the carinal level. Traction sutures were either placed circumferentially or only in the dorsal wall and the breaking strength—circumferential disruption of the muscular layer—was measured. Suture size (USP 4–0 vs. 5–0) was also evaluated in a similar way.Results Neither traction suture position did not influence breaking strengths between circumferentially placed traction sutures or those exclusively placed in the dorsal esophageal wall (Δ = 0.47 N, 95% confidence interval: −2.83 to 3.76 N, p = 0.771, n = 11 per group) nor differing suture sizes of USP 4–0 and USP 5–0 (Δ = 1.46 N, 95% confidence interval: −3.2 to 0.28 N, p = 0.0946, n = 9 per group) affected breaking strengths.Conclusion Suture size and suture positioning do not affect mechanical stability in Foker's procedure and therefore can be adapted as needed according to patient's anatomy and size.
Keywords: esophageal; suturing; traction procedure; esophageal surgery